On the National Identity of the 18th-Century Russian Art in the First Half of the 20th Century Publications - Karev, Andrey A. (Actual Problems of Theory and History of Art, 2021)
The history of the research into the specifics of the national artistic heritage is closely related to the identification of its significance and role in the world art history. The choice of the period under consideration results from the then interest in the Russian national art identity which in its turn was brought forth by the specifics of the national art studies evolution — from a vigorous pace of its contemporary forms development at the beginning of the last century towards the postwar ideologized academicism. The problem stems from the confrontation period between “the westerners” and “the slavophiles”. “The Art World” artistic group members who were the first to recognize the great artistic value of the 18th century creative legacy also got interested in the specifics of the Russian artistic school. They used to see the new Russian art to have been influenced by the foreign tradition for a long time. They assumed that it was until the end of the century that it acquired its own authenticity. Throughout the first decade of the Soviet Regime the national identity issue was far from the topical ones. The research into the inimitable originality of the Russian art assumed its top priority in the 1930s when the course towards social realism was proclaimed to be the mainstream doctrine. That brought forth an intense research of its origin. As a result the 18th century art tended to be recognized as a stage forerunning the 19th-century critical realism. An idea to blend the two principles — the folk and the realistic, gave birth to the formation of a new approach towards understanding the nature of the national. The acuteness of “the Western vs the Russian” antinomy was mitigated by conceptualization of a high demand for the Russian national culture, which is clearly seen in the works by N. N. Kovalenskaya. It was her who was the first to recognize the rapid development of the Russian national art to be the major feature of the Russian national specifics. Throughout the postwar decade the awareness of the significance of the realistic approach towards the national artistic authenticity was reinforced by the interest towards Old Russian cultural heritage. The end of the 1950s witnessed the completion of the cycle — the one born from the ideas of the mid-19th century, started on the verge of the centuries and continued by the Soviet art scholars, with inevitable respective ideological amendments being introduced.